On the consequences of the US withdrawal from the Kyoto-Bonn Protocol - Barbara Buchner; Carlo Carraro; Igor Cersosimo (Fondazione Eni Enrico Mattei (FEEM), 2001)
The US decision not to ratify the Kyoto Protocol and the recent outcomes of the Bonn and Marrakech Conferences of the Parties have important implications for both the effectiveness and the efficiency of future climate policies. Among these implications, those related with technical change and with the functioning of the international market for carbon emissions are particularly relevant, because these variables have the largest impact on the overall abatement cost to be borne by Annex B countries in the short and in the long run. This paper analyses the consequences of the US decision to withdraw from the Kyoto/Bonn Protocol both on technological innovation and on the price of emission permits (and, as a consequence, on abatement costs). A first goal is to assess the impact of the US defection on the price of permits and compliance costs when technological innovation and diffusion is taken into account (the model embodies international technological spillovers). A second goal is to understand for what reasons in the presence of endogenous and induced technical change the reduction of the price of permits is lower than in most empirical analyses recently circulated. A third goal is to assess the role of Russia in climate negotiations, its increased bargaining power and its eventual incentives to follow the US defections.
Keywords: H0; H2; H3; 330; Agreements; climate; incentives; negotiations; equity; policy; transfers; Klimaschutz; Umweltabkommen; Umweltschutzinvestition; USA